Biorisk management in microbiology laboratory / Ts Dr Noorlis Ahmad - Ahmad, Noorlis (UiTM Cawangan Negeri Sembilan, 2023)
Microbiology studies all living organisms that are too small to be visible to the naked eye. This includes bacteria, archaea, viruses, fungi, prions, protozoa, and algae, collectively known as 'microbes.' It began with the hobby of developing a microscope by Antoine Van Leeuwenhoek, a Dutch draper, and provided proper documentation of his observation. The field is concerned with the structure, function, and classification of such organisms and with ways of both exploiting and controlling their activities. These microbes play vital roles in nutrient cycling, biodegradation/biodeterioration, climate change, food spoilage, the cause and control of disease, and biotechnology. However, microbes are also versatile, like making life-saving drugs, manufacturing biofuels, cleaning up pollution, and producing/processing food and drink. Conventional microbiology is a laborious, expensive, and time-consuming exercise. However, modern and applied microbiology research has been. It continues to be central to meeting many current global aspirations and challenges, such as maintaining food, water, and energy security for a healthy population on habitable earth. There are techniques that define microbiology as a scientific field of study. It has been estimated that less than 1% of bacteria can be grown in a culture in a laboratory. Microbiologists culture bacteria by providing them with food, water, and other growth requirements in an environment with a constant and comfortable growth temperature.